2009
DOI: 10.4314/thrb.v8i3.45114
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and feeding practices of under-five children in Simanjiro District, Tanzania

Abstract: This study was undertaken to assess the nutritional status and feeding practices of <5 year children among the pastoral communities of Simanjiro district, northern Tanzania.. Face-to-face interviews with the sampled mothers were conducted using a semi-structured questionnaire. Anthropometric measurements using weight-for-age criterion were employed to assess the nutritional status. The study showed that 31% of the children were undernourished, some (6%) of them severely. Children 2 -3 years old were the most a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
42
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 0 publications
13
42
1
1
Order By: Relevance
“…The observed percentages of the underweight in this study were almost four times higher than the national standards reported in the 2010 Tanzania Demographic and Health Survey (URT, 2011), which revealed that 16% of Tanzanian under-five children studied during the survey were underweight, with Arusha region having the highest rates (28%). Nyaruhucha et al (2006) and Abubakar, Uriyo, Msuya, Swai, and Stray-Pedersen (2012) observed high underweight rates in northern Tanzania, in Manyara (31%) and Kilimanjaro (19%) respectively. The percentage of severely underweight children in our study (13%) was more than three times than the national rates (4%) (URT, 2011).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The observed percentages of the underweight in this study were almost four times higher than the national standards reported in the 2010 Tanzania Demographic and Health Survey (URT, 2011), which revealed that 16% of Tanzanian under-five children studied during the survey were underweight, with Arusha region having the highest rates (28%). Nyaruhucha et al (2006) and Abubakar, Uriyo, Msuya, Swai, and Stray-Pedersen (2012) observed high underweight rates in northern Tanzania, in Manyara (31%) and Kilimanjaro (19%) respectively. The percentage of severely underweight children in our study (13%) was more than three times than the national rates (4%) (URT, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Women and children, particularly the under-fives, are among the most vulnerable groups in areas that experience food insecurity, inadequate diets and undernutrition (Blössner & de Onis, 2005, Nyaruhucha, Msuya, Mamiro, & Kerengi, 2006; United Republic of Tanzania [URT] 2011;UNICEF 2012). Inadequate diet affects under-five children more than other age groups because under-fives grow rapidly, and need more nutrient-rich diet for their growth and development (Blossner & de Onis, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…; Nyaruhucha et al . ). Therefore, results of this study should be used by nutrition extension services to emphasise on the need for observance of exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 97%
“…; Nyaruhucha et al . ), as afore stated, in this country, the maize used for complementary foods is often contaminated with both aflatoxins and fumonisins (Kimanya et al . ; Manjula et al .…”
Section: Introductionmentioning
confidence: 90%
“…In most parts of Tanzania, maize is the main cereal used in complementary food (Mamiro et al . 2005; Nyaruhucha et al . 2006; Kimanya et al .…”
Section: Introductionmentioning
confidence: 99%